A Single-Center Retrospective Study to Identify Homocysteine Reference Intervals in Healthy Chinese 60 Years of Age and Above: Homocysteine Reference Intervals in the elderly - Zong, Jianmin; Sun, Yue (Journal of Medical Biochemistry, 2023)
SummaryBackground: Homocysteine (Hcy) are associated with many age-related diseases. Heterogeneous physiology with aging combined with unresolved assays standardization necessitates the establishment of specific Hcy reference intervals (RIs) applicable to the elderly. This retrospective study aimed to identify Hcy RIs in the elderly aged 60 years and older from a hospital in Jiangsu Province, China.Methods: Data from individuals undergoing routine physical examinations were collected. Hcy were measured on Hitachi 7600 analyzer using enzymatic cycling method. Outliers were identified by Dixon methods. Age- and gender-specific differences were estimated by nonparametric tests. Factors affected Hcy were assessed using multivariate linear regression. RIs with 90% confidence intervals were determined by nonparametric method.Results: A total of 2594 individuals were included. Hcy levels increased with age(r=0.248, p
Keywords: homocysteine, reference intervals, indirect methods, aged